Penanaman Edukasi Mitigasi Bencana pada Masyarakat Jepang - Arsi Widiandari (KIRYOKU, 2021)
Research related to disaster mitigation is still an interesting topic to discuss. Moreover, Japan is also a disaster-prone country. The focus of this research is to discuss the cultivation of disaster mitigation education and how it is implemented in Japanese society. This study uses the literature method because it is considered the most appropriate and possible due to limited space. By taking data from official reports published by the Japanese government as secondary data, this research article will try to discuss the effectiveness of disaster education carried out by Japanese society. This study found that there are several keys to the success of disaster mitigation education carried out by Japan, including the role of educational facilitators, the role of central and local government, the existence of disaster response organizations and community cooperation as a whole. This paper is expected to complement previous research related to disaster knowledge. Thus, it is hoped that it can provide benefits especially to Indonesia, which is also a country that is quite often hit by natural disasters.